The Interaction Between Arabic and Bahasa Melayu in Traditional Islamic Schools in Bangkok: An Analysis and Alternative Approach - Yenprasit , Prasert; Naknawa, Dulyawit (Millah: Journal of Religious Studies, 2025)
Traditional Islamic schools are institutions where Arabic and Bahasa Melayu function together as mediums for Islamic learning. This research aims to explore, analyze, and propose strategies for utilizing both Arabic and Bahasa Melayu in teaching. The data was collected through field survey and in-depth interview with 15 teachers and 25 students from 5 traditional Islamic schools that employ Arabic and Bahasa Melayu in their curricula. The findings revealed that Bahasa Melayu represents regional Islam, while Arabic serves as the global language of Islam. In the context of Bangkok, most Muslims are Melayu descent who adapted to Thai culture. Although they may not be able to preserve their Melayu identity in term of language, they can connect their Muslim identity with the Bahasa Melayu in traditional Islamic schools through religious education. Understanding the interaction between Arabic and Bahasa Melayu in this context requires consideration of languages, identity preservation, and cultural heritage. Moreover, this will suggest traditional Islamic schools to develop Arabic and Bahasa Melayu teaching and instruction. To express both global and regional Muslim identities within the context of Bangkok, the capital city with a strong Thai identity.